Effects of contrast strength training with elastic band program on sprint, jump, strength, balance and repeated change of direction in young female handball players. Issue 5 (October 2022) - Hammami, Mehrez; Gaamouri, Nawel; Cherni, Yosser; Chelly, Mohamed Souhaiel; Hill, Lee; Knechtle, Beat
Maximal strength, power and his derivates (sprint, change of direction repeatedly and jump) are considered as major determinants of success in elite handball players. Contrast strength training with elastic band (CSTEB) program is form of resistance training, and may play an important method of training to improve this quality. This study examined the effects of 10-week contrast strength training with elastic band (CSTEB) program on physical performance in young female handball players. Thirty participants (age: 15.7 ± 0.3 years; body mass: 63.7 ± 3.7 kg; body height: 166.8 ± 3.8 cm; body fat: 26.9 ± 3.4; and Maturity-offset: 2.9 ± 0.3 years) were randomly assigned between experimental group (EG; n = 15) and control group (CG; n = 15). Two-way analyses of variance (group × time) were assessed for handgrip; back extensor; medicine ball throw; 30-m sprint times; Modiﬁed Illinois change-of-direction (Illinois-MT); four jump tests [(squat jump (SJ), countermovement jump (CMJ), countermovement jump with arms (CMJA) and five jump test (5JT)]; static (stork) and dynamic (Y balance) balance tests; and repeated sprint T-test (RSTT). The EG enhanced all strength performance [handgrip right, handgrip left, back extensor strength and medicine ball throw (p < 0.001)] compared to CG. The EG enhanced all sprint performance. The EG also improved performance in the Illinois-MT. All jump performance improved signiﬁcantly [SJ (p = 0.007), CMJ (p = 0.001) and CMJA (p = 0.001)] except 5JT in the EG. Of the same, 3 of 4 repeated sprint T-test scores [RSTT-Best-Time, RSTT-Mean-Time and RSTT-Total-Time] increased significantly in the EG relative to the CG. Conversely, there were no significant changes in balance performance between groups. It is concluded that 10-weeks of CSTEB improved physical performance (strength, sprint, change of direction, jump, and repeated change of direction) measures in young female handball players.